Analisis Kebijakan Luar Negeri Australia: Studi Kasus Penguatan Ketahanan Pangan Indonesia (2013-2021) [Australia Foreign Policy Analysis: The Study Case of Indonesia Food Security Strengthening (2013-2021)] - Patricia Onasis Theda; Elyzabeth Bonethe Nasution; Qanszelir GB Pandjaitan XIV (Universitas Pelita Harapan, 2023)
Australia and Indonesia have a turbulent relationship. One of Australia's foreign policies towards Indonesia is assistance in efforts to strengthen Indonesia's food security through the Australia-Indonesia Partnership for Promoting Rural Incomes through Support for Markets in Agriculture (AIP-PRISMA) program. This is indeed unique, considering that Australia usually supports food security globally or specifically to countries on the continent of Oceania and underdeveloped countries. This research is conducted to examine the factors that influenced Australia in implementing the program and the impact the program gives as an effort to strengthen Indonesia's food security. This research uses a qualitative approach; explanatory, case study, and descriptive methods; and narrative and illustrative analytical techniques. The data used is collected through literature studies and online searches. The research employs Constructivism theory, with the concept of identity and action, the logic of appropriateness, national interest, and foreign policy. This research focuses on the elaboration of Australia's identity and its foreign policy orientation towards a country it considers important, such as Indonesia. The results of the research show that the implementation of the AIP-PRISMA program is driven by Australian identity and national interests. The AIP-PRISMA program itself has succeeded in strengthening Indonesia's food security, especially in Eastern Indonesia. Subsequently, the implementation of the program in turn helped Australia achieve its national interests.Bahasa Indonesia Abstract: Australia dan Indonesia memiliki hubungan yang dipenuhi dengan gejolak. Salah satu kebijakan luar negeri Australia terhadap Indonesia adalah bantuan dalam upaya penguatan ketahanan pangan Indonesia melalui program Australia-Indonesia Partnership for Promoting Rural Incomes through Support for Markets in Agriculture (AIP-PRISMA). Hal ini tergolong unik, mengingat Australia biasanya mendukung ketahanan pangan secara global atau secara khusus ke negara di Benua Oceania dan negara-negara terbelakang. Penelitian ini dilakukan untuk menelaah faktor-faktor yang memengaruhi Australia dalam menjalankan program tersebut dan dampak penerapan program terhadap upaya penguatan ketahanan pangan Indonesia. Penelitian ini menggunakan pendekatan kualitatif; metode eksplanasi, studi kasus, dan deskriptif; serta teknik analisis naratif dan ilustratif. Data yang digunakan dikumpulkan melalui studi kepustakaan dan penelusuran daring. Kemudian, teori yang digunakan dalam penelitian ini adalah teori Konstruktivisme dengan konsep identitas dan aksi, logic of appropriateness, kepentingan nasional, dan kebijakan luar negeri. Penelitian ini berfokus pada penjabaran terhadap identitas Australia serta orientasi kebijakan luar negerinya terhadap negara yang dianggapnya penting seperti Indonesia. Hasil penelitian menunjukkan bahwa penerapan program AIP-PRISMA didorong oleh faktor identitas dan kepentingan nasional Australia. Program AIP-PRISMA sendiri berhasil memperkuat ketahanan pangan Indonesia, khususnya di Indonesia Timur. Penerapan program tersebut pada akhirnya membantu Australia dalam mencapai kepentingan nasionalnya.